Fall-sown cover crops as mulches for weed suppression in organic small-scale diversified vegetable production. Issue 4 (27th July 2016) - Bietila, Eric; Silva, Erin M.; Pfeiffer, Anne C.; Colquhoun, Jed B.
Abstract: Cover crop-based reduced tillage (CCBRT) has achieved positive impacts in organic row crop systems, contributing to the conservation of soil resources and the facilitation of weed management. This technique, which uses cover crop residues as mulches to suppress weeds, has shown more variable success in organic vegetable production systems. This experiment examined CCBRT for small-scale organic vegetable production in the upper Midwestern USA, specifically evaluating weed suppression, labor inputs and crop yields. Cereal rye ( Secale cereale L.) and winter wheat ( Triticum aestivum L.) were fall-sown in 2012 and 2013 in a strip-plot design, including control treatments with no cover crop and spring-applied oat straw mulch. Cover crop plots were strip-tilled in mid-April to establish a planting zone, with cover crops terminated in late May at anthesis with a hand-tractor mounted sickle-bar mower. Bell peppers ( Capsicum annuum L. var. 'Revolution'), snap beans ( Phaseolus vulgaris L. var. 'Tavera'), and potatoes ( Solanum tuberosum L. var. 'Red La Soda') were hand-planted either as transplants or seed in each treatment immediately following cover crop termination. During each summer growing season, weeds were completely eliminated from each plot by hand approximately every 10–14 days, with time for manual weeding recorded for each treatment. Vegetable crop yields and quality were measured at harvest during 2013 and 2014. Cereal rye and winter wheat produced similar biomass at the time of termination. Greater weed biomass was collected in the wheat treatment as compared with the cereal rye, increasing the in-season labor required for manual weeding. Bean yields were decreased in the all CCBRT treatments compared with control treatments in both years of the study. Pepper yields did not differ in CCBRT treatments as compared with the control in both 2012 and 2013, although the CCBRT treatments did yield lower marketable peppers compared with the straw mulch plots. Potato tuber yields were not different in the CCBRT treatments as compared with the control in 2012, but were lower in 2013. These data indicate that, if CCBRT is to be more widely adopted in small-scale vegetable production, further optimization of the system must be achieved to ensure consistent and adequate weed suppression while maintaining crop yield and quality.